Formulation and Characterization of Dental Film Containing Ofloxacin - Md. Sajid Ali, Javed Ali, Alka Ahuja, Md. Sarfaraz Alam (Journal of Applied Pharmaceutical Science)
The aim of the study was to formulate intrapocket dental films, which could be easily placed into the periodontal pocket, and be capable of delivering therapeutic concentrations of ofloxacin for prolonged period of time at a much lower dose, hence obviating untoward side effects. Intrapocket device containing ofloxacin was prepared using 255.20 mg of ofloxacin, 2.0% plasticizer diethyl phthalate and 1.4g ethyl cellulose. The device was optimized on the basis of evaluation parameters such as weight variation, content uniformity, surface pH, in vitro and in vivo release studies. Films showed sustained in vitro release for a period of 11 days. In vivo release studies showed that drug concentrations were maintained above MIC value for entire period of release studies. The samples from this study were capable of inhibiting the growth of most test strains. Ofloxacin in carrier polymer ethyl cellulose showed extended spectrum of antimicrobial activity. Stability studies were conducted on optimized formulation and degradation rate constant was found to be 1.2056 × 10-4/day. The drug released locally and had high benefit to low risk ratio as compared to systemic administration, which is unacceptable due to, low benefit to high-risk ratio. Hence low dose site-specific films is a better alternative.
Keywords: Periodontal disease,intrapocket device,ofloxacin,microbiological studies